2007
DOI: 10.1097/01.pcc.0000253026.67341.5d
|View full text |Cite
|
Sign up to set email alerts
|

Use of levosimendan, a new inodilator, for postoperative myocardial stunning in a premature neonate

Abstract: In this premature neonate with postoperative low cardiac output syndrome due to failing myocardial function, levosimendan was a potent inotropic agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 10 publications
1
29
0
2
Order By: Relevance
“…Low grade evidence data exists in the form of a case report about its use in preterm population with improvement in LVO post-cardiac surgery [64].…”
Section: Discussionmentioning
confidence: 99%
“…Low grade evidence data exists in the form of a case report about its use in preterm population with improvement in LVO post-cardiac surgery [64].…”
Section: Discussionmentioning
confidence: 99%
“…As opening of myocardial K ATP channels plays a key role in the mediation of ischemic preconditioning, one may speculate that administration of the K ATP channel opener levosimendanbefore ischemia may also prevent or attenuate the negative effects of myocardial stunning. recent small studies have repeatedly demonstrated ap ossible valuable role of levosimendan in the frequently observed setting of myocardial stunning (12)(13)(14).…”
Section: Myocardial Stunningmentioning
confidence: 99%
“…In several studies, levosimendan was found to increase the heart contraction force and stroke volume of patients with myocardial stunning [3,4,5,6]. The goal of this study was to evaluate the efficacy of levosimendan for treating myocardial stunning after emergency PCI in patients with AMI.…”
Section: Introductionmentioning
confidence: 99%